Exploring student and lecturer perceptions of web blogging as an alternative tool for language assessment - Nipunika Dilani (Technology in Language Teaching & Learning)
This study explores student and lecturer perceptions of web blogging as an alternative assessment tool for language testing in the Sri Lankan context. Rooted in constructivism, the research investigates how web blogging engages learners in meaningful language use and reflects real-world communication. The study seeks to identify (i) What language skills can be effectively assessed through web blogging? (ii) How do Sri Lankan students and lecturers perceive the use of web blogging as an alternative assessment method? (iii) What challenges do students face when creating web blogs for language assessment? and (iv) What challenges do lecturers encounter in assessing language skills through web blogs? A qualitative approach was employed, using open-ended questionnaires for students and lecturers and content analysis of the student-created web blogs to gather rich, contextual data. The findings reveal that blogging supports the assessment of various language skills and soft skills while also fostering learner autonomy and engagement. However, challenges such as digital access, workload, and assessment criteria were noted. The study concludes that, despite some limitations, web blogging holds strong potential as a student-centered alternative to traditional language assessments.